Mathematical modeling of thin-layer drying of shrimp (Global Journal of Science Frontier Research, 2012)
In this study, microwave drying behaviour of shrimp was investigated. The drying study showed that the times taken for drying of shrimp from the initial moisture contents of 3.103% (d.b.) to final moisture content of around 0.01% (d.b.) were 11.75, 7, 4.75 and 4 min in 200, 300, 400 and 500W, respectively. The drying data were fitted to 7 thin-layer drying models. The performances of these models were compared using the determination of coefficient (R 2 ), reduced chi-square (χ 2 ) and root mean square error (RMSE) between the observed and predicted moisture ratios. The results showed that Midilli model was found to satisfactorily describe the microwave drying curves of shrimp. The activation energy for moisture diffusion was found to be 12.834W/g.
Keywords: microwave drying; shrimp; modeling